Implementasi Standar PAUD Nomor 137 Tahun 2014 (Standar Isi, Pengelolaan, Sarana Prasarana) dalam Penyelenggaraan Pendidikan Anak Usia Dini Al-Qur’an (PAUDQU) di Kecamatan Parongpong Bandung Barat : Implementation of PAUD Standards Number 137 of 2014 (Content Standards, Management, Infrastructure) in the Implementation of Early Childhood Al-Qur'an Education (PAUDQU) in Parongpong District, West Bandung - Adawiyah, Elis; Masnipal; Mubiar Agustin (Litera Academica Publishing, 2024)
The presence of PAUDQu in Indonesia is increasingly widespread. All PAUD organizers, including PAUDQu, must be guided by National Education Ministerial Decree No. 137/2014. This research aims to determine the implementation of content, management and infrastructure standards based on Permendikbud No. 137/2014 in the implementation of PAUDQ. The method used is qualitative descriptive. The data source was obtained from respondents from PAUDQu institutions in Parongpong sub-district, West Bandung Regency. Data collection techniques using observation, interviews and documentation. The collected data was then analyzed using data triangulation techniques. This research concludes that the implementation of PAUDQu in implementing content standards and infrastructure standards is in accordance with PAUD Standards Permendikbud number 137 of 2014. However, in implementing management standards it is not yet in accordance with the Management Standards contained in Permendikbud number 137 of 2014 as it has not been fully implemented in the plan work and supervision.